Resiliensi Perempuan Dewasa Awal Atas Beban Pertanyaan Kapan Menikah (Universitas Muhammadiyah Metro, 2023)
Individuals have developmental tasks that must run according to their phase. Early adulthood is the peak phase of life where each individual has the developmental task of getting a job, choosing life friends and building a family. The benchmark of individual success in life is the completion of developmental tasks. If even one developmental task has not been completed, the individual will make other developmental tasks hampered so that it can trigger stress and inner pressure. Early adult women who are not married at the age of 30 will become a burden due to demands in society. Society demands by asking the question when to get married. The question of when to get married is not a simple question but a question that becomes a serious problem. The focus of the research that will be conducted is to see how the resilience of early adult women who are not married at the age of 30 years. This research uses a qualitative method with a phenomenological approach. The research sources are two unmarried early adult women. The data analysis technique uses thematic analysis. From the results of this study found the theme of the description of individual resilience in facing the question of when to get married. The interpersonal ability of the informants to share stories with a trusted figure to relieve the burden of the question. Competence and self-regard owned by the informant in overcoming anxiety over the burden of late marriage and finally the informant was able to think positively about the difficulties he experienced. The suggestion of the question of when to get married is a question that puts a burden on unmarried women, the burden and anxiety is a natural thing but it requires individual ability not to focus on the question.